2006
DOI: 10.2205/2006es000206
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentogenesis in Maastrichtian-Danian basins of the Russian plate and adjacent areas in the context of plume geodynamics

Abstract: The sediment composition and sedimentation conditions of Maastrichtian and Danian deposits in the vast territory of the Russian plate and adjacent regions of North Eurasia were studied. The succession of Late Cretaceous carbonaceous conditions of sedimentation in the Early Paleocene is noted in the major part of North Eurasia sedimentary basins. In some areas of the Lower Volga region and of the Northern Cis-Caspian basin, a radical change occurred in the sedimentation conditions at the Cretaceous-Paleogene bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…The content of metallic iron in this layer from the five separated sections varies widely: it is absent or, more precisely, has not been detected by TMA, in 19 samples out of 28 studied and varies from 0.0001 to 0.002% in the remaining nine samples [Grachev et al, 2005;Molostovsky et al, 2006;Pechersky, 2008;Pechersky et al, 2006aPechersky et al, , 2006b]; (D. M. Pechersky et al, in press, 2008a,b). A detailed imbedded study of the boundary layer from the Gams section showed that metallic iron is present only in the upper and lower parts of this layer (Figure 1).…”
Section: Es6006mentioning
confidence: 99%
See 3 more Smart Citations
“…The content of metallic iron in this layer from the five separated sections varies widely: it is absent or, more precisely, has not been detected by TMA, in 19 samples out of 28 studied and varies from 0.0001 to 0.002% in the remaining nine samples [Grachev et al, 2005;Molostovsky et al, 2006;Pechersky, 2008;Pechersky et al, 2006aPechersky et al, , 2006b]; (D. M. Pechersky et al, in press, 2008a,b). A detailed imbedded study of the boundary layer from the Gams section showed that metallic iron is present only in the upper and lower parts of this layer (Figure 1).…”
Section: Es6006mentioning
confidence: 99%
“…Correlation between paramagnetic magnetization (Mp) and concentration of ferromagnetic Fe-hydroxides (goethite), magnetite, titanomagnetite, and metallic iron in sediments. The data for the Gams, Koshak, Klyuchi, Teplovka, Tetritskaro, and Khalats sections are combined [Molostovsky et al, 2006;Pechersky et al, 2006aPechersky et al, , 2006bPechersky, 2008]; (D. M. Pechersky et al, in press, 2008a,b). particles of terrestrial origin; and "secondary" as a result of subsequent oxidation of metallic iron particles with formation of Fe-hydroxides and hematite.…”
Section: Temporal Distribution Of Metallic Ironmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern data on distribution of native iron and nickel in the cosmic dust is rather limited, since only "direct" methods of detecting such particles were used. Thermomagnetic analysis (TMA) up to 800ºC was employed during petromagnetic (rock-magnetic) studies of sediments [1][2][3][4][5][6][7]. The increase of ТMA temperature interval by 100 о has given the chance to observe a detailed picture of a distribution of metallic iron in space and time.…”
Section: Introductionmentioning
confidence: 99%